2018
DOI: 10.3390/ijerph15040729
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Quality Gaps in TB Screening in South Africa Using Standardised Patient Analysis

Abstract: This is the first multi-district Standardised Patient (SP) study in South Africa. It measures the quality of TB screening at primary healthcare (PHC) facilities. We hypothesise that TB screening protocols and best practices are poorly adhered to at the PHC level. The SP method allows researchers to observe how healthcare providers identify, test and advise presumptive TB patients, and whether this aligns with clinical protocols and best practice. The study was conducted at PHC facilities in two provinces and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 38 publications
0
51
1
Order By: Relevance
“…Christian et al explored the quality of HIV and TB health care provision in the Western Cape and its alignment to the national protocols. They cited that only 43% of cases met the minimum threshold for adequate case management and protocol deviations could be attributed to poor training and knowledge, deficiencies in monitoring and the lack of clinical governance [37]. They reported consistently poor information sharing by the staff; and the importance of returning for TB results was only discussed in a third of interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Christian et al explored the quality of HIV and TB health care provision in the Western Cape and its alignment to the national protocols. They cited that only 43% of cases met the minimum threshold for adequate case management and protocol deviations could be attributed to poor training and knowledge, deficiencies in monitoring and the lack of clinical governance [37]. They reported consistently poor information sharing by the staff; and the importance of returning for TB results was only discussed in a third of interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there was no objective measure of whether the patients had been adequately informed about the disease or its management. The overall findings from the Western Cape study suggested low effort in communicating invaluable information regarding untreated TB and the need for treatment and acknowledged that the poor adherence to the protocols were possibly resulting in the disappointing TB outcomes [37].…”
Section: Discussionmentioning
confidence: 99%
“…Ensure universal TB screening -Clinics should screen everybody coming into the clinic who is not currently on tuberculosis treatment. Yet, currently our data suggest that either this is not happening or it is being poorly recorded 52 .…”
Section: Recommendationsmentioning
confidence: 71%
“…Christian et al explored the quality of HIV and TB health care provision in the Western Cape and its alignment to the national protocols. They cited that only 43% of cases met the minimum threshold for adequate case management and protocol deviations could be attributed to poor training and knowledge, deficiencies in monitoring and the lack of clinical governance (38). They reported consistently poor information sharing by the staff; and the importance of returning for TB results was only discussed in a third of interactions.…”
Section: Exploredmentioning
confidence: 99%
“…Consequently, there was no objective measure of whether the patients had been adequately informed about the disease or its management. The overall findings from the Western Cape study suggested low effort in communicating invaluable information regarding untreated TB and the need for treatment and acknowledged that the poor adherence to the protocols were possibly resulting in the disappointing TB outcomes (38).…”
Section: Exploredmentioning
confidence: 99%